2010
DOI: 10.1086/652469
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection on Testosterone Production in a Wild Songbird Population

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: Because of their role in mediating life-history trade-offs, hormones are expected to be strongly associated with components of fitness; however, few studies have exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 95 publications
(153 reference statements)
4
91
0
Order By: Relevance
“…In socially monogamous and biparental species, only a single study found a relationship between circulating GnRH-induced testosterone levels and reproductive success. In contrast to the studies on polygynous species, selection on testosterone levels in dark-eyed juncos (Junco hyemalis) was stabilizing: males with slightly higher than average testosterone concentrations had the highest reproductive success and were most likely to survive (McGlothlin et al, 2010). On the other hand, in a study on North-American barn swallows (Hirundo rustica erythrogaster) no relationship between testosterone levels and total number of offspring was found (Eikenaar et al, 2011).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…In socially monogamous and biparental species, only a single study found a relationship between circulating GnRH-induced testosterone levels and reproductive success. In contrast to the studies on polygynous species, selection on testosterone levels in dark-eyed juncos (Junco hyemalis) was stabilizing: males with slightly higher than average testosterone concentrations had the highest reproductive success and were most likely to survive (McGlothlin et al, 2010). On the other hand, in a study on North-American barn swallows (Hirundo rustica erythrogaster) no relationship between testosterone levels and total number of offspring was found (Eikenaar et al, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…Thus, it is likely that natural variation in testosterone relates differently to within and extra-pair reproductive success depending on the species studied. In their study on darkeyed juncos, McGlothlin et al found that after partitioning reproductive success into within-and extra-pair reproductive success, selection on testosterone was directional and positive with respect to within-pair reproductive success, but it was stabilizing with respect to extra-pair mating success (McGlothlin et al, 2010). In contrast, in North-American barn swallows, testosterone levels during mating neither correlated with withinnor with extra-pair mating success (Eikenaar et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although selection is generally viewed as a driving force of evolutionary change, many adaptive phenotypic characters are under strong stabilizing selection and presumably have remained unchanged for long periods of evolutionary history (Price and Lanyon, 2002;McGlothlin et al, 2010). As an example, numerous studies show that the songs and conspicuous red epaulets of male redwinged blackbirds (Agelaius phoeniceus) are important sexuallyselected signals that clearly influence male success (Searcy and Yasukawa, 1995).…”
Section: Rates Of Evolutionary Change Do Not Necessarily Indicate Levmentioning
confidence: 99%